Financing small and medium sized enterprises in Mongolia - Munkhsoyol, Baatarjav; Ramachandran, Neelakantan; Sununta Siengthai; Tocquer, Gerard A.; Japanese Government (Pathum Thani, Thailand : Asian Institute of Technology, 2001)
The Mongolian economy is at a critical turning point. There have been important achievements in recent years. Major progress has been made in stabilization. The single- digit annual inflation rate for the period since 1997 has been significant milestone. Six consecutive years of positive real growth in the economy are almost certain to be extended to a seventh year in 2001. The reinvigoration of the privatization process since early 1997 has generated new momentum toward the creation of a private sector-led economy. However, recently, the economy has started to slow down. Many problems make the government head ache such as the growth rate of GDP is declining, unemployment is increasing, income gap and imbalance become bigger between rural and urban areas, the FDI is declining, or export grow at negative rate. These issues imply that it is time for the government to have another deeper reform to boost its economy for the sustainable development. Promotion and development of small and medium enterprises (SMEs) could be one of the promi~ng solutions to solve the problems. SME's position is still weak in the national economy. They receive little support from the government. This led they are meeting a lot of troubles in their businesses. Of these troubles, financing issue is the most important and obvious one to development of the SMEs at present. This research study tries to look at the issue of problems and prospects of SMEs development in Mongolia. This report provides an overall overview about the economy to understand the situation of the economy and the need for the promotion of SMEs in Mongolia. The research reviews the position of SMEs in the economy, as well as the importance of external finance to them. Correspondingly it examines sources of funds for the SMEs in general. One of the issues addressed in the research is investment decision-making referring to capital budgeting; which is crucial in enhancing the profitability and growth of enterprises. The 'right' commitment of current resources into long-term investments in order to secure a stream of cash flows in the future is vital importance as they generally involve high amounts of capital, and it is difficult to reverse the decision. The research study also identifies difficulties in the SMEs financing in Mongolia and explores the reasons for the difficulties faced by SMEs. Final chapter addresses recommendation and suggestion for improving the situation.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Business Administration, School of Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2001
Keywords: Small enterprises -- Mongolia; Small business -- Mongolia -- Finance